Polarization and site dependence of interatomic relaxation effects in double core hole states - Tashiro, Motomichi; Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S.; Ehara, Masahiro (Journal of physics. B, Atomic, molecular and optical physics, 2013)
The interatomic relaxation (IR) effects of two-site double core hole (tsDCH) states in selected molecules with a polarizable unit have been systematically investigated using ab initio calculations. The IR effects are analysed by varying the size of this polarizable unit and its position relative to the DCHs. The systems with the DCHs located on the opposite sides of the polarizable unit show large negative IR energies, while those on the same side of the polarizable unit have smaller negative IR effects. Here, the IR energies can even be positive if the polarizable unit is large enough. The generalized Wagner plots of tsDCH states are used to visualize the trend of the IR effects in the molecules studied.
Gesehen am 31.01.2022